Spontaneous pneumomediastinum in the Young adult "Hamman’s syndrome": Case report - Serna-Trejos, Juan Santiago; Castro-Galvis, Carlos Andrés; Bermudez-Moyano, Stefanya Geraldine; Rivera-Villegas, Carlos Felipe; Márquez-Flórez, Vanessa (Cirugía del Uruguay, 2025)
Hamman syndrome is a rare condition, generally benign in nature, characterized by the presence of spontaneous pneumomediastinum without apparent cause. Although its prognosis is usually favorable, diagnosis must be based on the exclusion of potentially serious secondary causes, such as trauma, tracheobronchial or esophageal injuries, which require a different approach and may be life-threatening. We present the case of a previously healthy 20-year-old male who consulted for sudden-onset neck pain with no relevant clinical history. Radiological examination revealed pneumomediastinum, with no findings suggesting a secondary etiology. Given the confirmation of its spontaneous nature, conservative management based on rest, analgesia, and close clinical monitoring was instituted, with satisfactory progress and complete resolution of the condition. This case illustrates the importance of a comprehensive diagnostic approach that combines clinical assessment, imaging studies, and follow-up, avoiding unnecessary invasive procedures and reinforcing the role of noninvasive treatment in patients with confirmed spontaneous pneumomediastinum.